PERVAPORATION OF WATER-ETHANOL MIXTURE THROUGH HYDROPHILICALLY MODIFIED POLYIMIDE MEMBRANE - KANG, YS; JUNG, BS; KIM, UY (GORDON BREACH SCI PUBL LTD, 1993)
Polyimide of pyromellitic dianhydride (PMDA) and 4,4'-oxydianiline (ODA) was hydrophilically modified by partial replacing of ODA with 3,5-diaminobenzoic acid (DABA) containing a carboxylic group with two amine groups. Pervaporation experiments of water/ethanol mixture were performed and the results demonstrated that both flux and permselectivity increase simultaneously with increasing DABA content in polyimide backbone. From the sorption and temperature-dependent permeation behavior, it could be concluded that the diffusivity of permeant plays a major role in determining the pervaporation performance rather than the solubility.
Keywords: SELECTIVE SEPARATION; PERMEATION; ACID